A Effectiveness of PjBL-STEM on Based Chemistry E-Modules on Chemical Reaction Material on the Learning Outcomes of Phase E Students - Nadia, Nadia Afrianti; Yerimadesi, Yerimadesi (Journal of Classroom Action Research, 2024)
This research focused on analyzing effectiveness of the PjBL-STEM based on Chemistry E-module on the topic of chemical reactions on the learning outcomes of SMAN 4 Padang E stage students. The type of research used fell into the category of quasi-experimental research and used design of a non-equivalent control group design. Population consisted of students from Class X E stage, and the sampling was done using the purposive sampling method. Class XE4 was selected as the experimental group, and Class XE3 was selected as the control group. The research instrument included tests to measure learning outcomes, and its validity, reliability, difficulty index, and uniqueness were validated. The data were statistically analyzed using test of n-gain, normallity, homogeneity, and hypothesis. Due to the normal distribution and homogeneity of the data, hypothesis testing was performed using t-test. Based on the data obtained, n-gain value of the experimental group was 0.73, which was classified as high, while the n-gain value of the control group was 0.66, which was classified as medium. The results of the hypothesis test showed that the Sig value (2-tailed) was less than 0.05, resulting in the rejection of H0 and the acceptance of H1. This indicates that the students of learning outcomes who were instruct chemical reaction materials using PjBL-STEM based chemical electronics module were significantly higher than those of students who didn’t use the electronics module in the E phase of SMAN 4 Padang. In conclusion, the use of the PjBL-STEM based chemical electronics module on chemical reaction materials can effectively improve students' learning outcomes.